PENYULUHAN KEBERSIHAN DIRI SAAT MENSTRUASI PADA SISWI SMPN 3 KURIPAN LOMBOK BARAT - Irni Setyawati; Kusniyati Utami; Dian Soekmawaty Riezqy Ariendha (Stikes Yarsi Mataram, 2021)
WHO said that adolescence is a period of rapid physical, cognitive, and psychosocial growth [2]. The physical growth of this teenager is marked by menstruation as the beginning of entering the puberty process [3]. Menstruation is regular bleeding from the uterus as a sign that the uterine organs are functioning properly. At this time the uterine blood vessels are very susceptible to infection and can cause diseases of the reproductive tract, urinary tract infections, and skin irritation, therefore cleanliness must be maintained [1,3]. Based on the results of research in 2019 at SMPN 3 Kuripan it was found that the level of knowledge of most of the VII and VIII grade students about personal hygiene during menstruation was still lacking [6]. Partners already have a UKS unit, but the students have never received information about personal hygiene during menstruation either from the local health service agency or the school. Based on the problems above, community service